A Multimodal Approach to the Management of Diverticular Abscess with Paraesophageal Hernia Complication - Pauliana, Pauliana; Koncoro, Hendra; Prawidiyanto, Albertus Ardian; Gora, Cosmas; Irman, Irman; Tambun, Renaningtyas (Syntax Corporation, 2024)
This study aims to evaluate the management of acute diverticulitis complicated by hernia and the role of electroacupuncture in managing postoperative ileus. The case involved a 51-year-old male patient who presented with left lower abdominal pain, fever, and defecation disorder. Physical examination showed signs of infection with localized peritonitis, while laboratory tests revealed neutrophilia. CT scan showed diverticulitis with abscesses in the descending and sigmoid colon, as well as free air around the colon and perihepatic region, and paraesophageal hernia. The patient underwent left hemicolectomy with Hartmann's procedure. Postoperatively, the patient developed ileus which was treated using electroacupuncture. The results showed that the relationship between diverticulosis and hernia is due to connective tissue changes. Approximately 10-20% of diverticulosis cases progress to acute diverticulitis. CT scan is the gold standard for diagnosis, staging and management of diverticulitis. In cases of Hinchey III diverticulitis, laparoscopic washing does not give better results compared to colonic resection. The Hartmann procedure is recommended for patients with multiple comorbidities. Electroacupuncture proved to be an effective adjunctive therapy in managing postoperative ileus. The conclusion of this study is that a multimodal approach, including surgery and complementary therapies such as electroacupuncture, is essential in the management of diverticulitis and its complications. The implication of this study is the need for a holistic approach in managing patients with acute diverticulitis, especially in cases with multiple comorbidities and risk of postoperative complications.